Drug Handbook in Obstetrics and Gynaecology - Debdas, A. K. (Jaypee Brothers Medical Publishers, 2022)
The aim of this handbook is to focus on the drug in obstetrics and gynaecology. Thoroughly revised, updated and user-friendly edition, this book is an instant medicine guide for pregnancy, covering medical disorders in pregnancy. This book is divided into two parts: Obstetrics and Gynaecology. This book is designed to serve as a quick 'medicine memory aid' for the busy obstetricians, physicians, and general practitioners to answer their ever-haunting queries about prescribing in pregnancy, such as-Which antibiotic, Which anti-emetic, Which anti-hypertensive, Which anti-tubercular, At which dose, At what frequency, For what duration, In which trimester, What about advisability regarding breast-feeding, etc. Treatment of gynaecological disorders is essentially drug dependent. Besides, with the increasing availability of ultraprecise sophisticated investigation and monitoring facility, the medical options of treatment for gynaecological disorders are also increasing, e.g., ectopics now can be treated medically, first trimester abortion can be achieved by drugs alone, fibroids can be made to shrink by drugs, etc. This ready-reckoner has been designed to cope with all the above and more and instantly. The major beneficiary of this ready-reckoner will be internees, young house officers and obstetrics and gynaecology postgraduates, who must carry the book all the time in their pocket to rescue them at every practical situation, they would have to face, whether in outpatient department (OPD) or ward or emergency room of the obstetrics unit. For undergraduate students, it will be like 'pre-exam pill' for tiding over both theory and viva of obstetrics and gynaecology.